Competitiveness of African agricultural value chains - Dedehouanou, Fidele; Dimaranan, Betina; Laborde Debucquet, David (International Food Policy Research Institute, 2019)
This chapter uses a statistical approach to explore African agricultural competitiveness. We illustrate competitiveness through all three means mentioned above: microeconomic drivers, macroeconomic drivers, and impact. We discuss the evolution of Africa’s competitiveness, comparing the competitiveness of Africa’s regional economic communities (RECs) with the world and among each other. We also analyze the competitiveness of value chains by commodity for the commodity value chains that are most significant for Africa’s trade. We examine the various macroeconomic factors, especially the real effective exchange rate, that affect the performance of each value chain in the world market.